REGULARITIES OF LEARNING AS A LANGUAGE METHODOLOGICAL PROBLEM (Pedagogy of Higher and Secondary Education, 2022)
The article gives the analysis of teaching regularities system, criteria that are put as a basis for the regularities are defned. The auhor pays special attention to the regularities in teaching the Ukrainian language.
Keywords: regularity; teaching component; interconnection; conditions of stucying